Implementasi Terapi Bermain Lego pada Pasien Anak Usia Pra Sekolah yang Menjalani Hospitalisasi dengan Masalah Kecemasan - Woran, Develin (JURNAL ILMIAH KESEHATAN MANADO, 2025)
Children are individuals who have different characteristics according to their age period. Hospitalization is a condition that requires children to receive treatment in hospital. This can make children afraid, cry, stressed/anxious, and even refuse treatment. One of the impacts of hospitalization is anxiety. Anxiety is the impact of hospitalization experienced by children because they face stressors in the hospital environment. Play therapy is an activity that can be done to get pleasure or satisfaction. Playing can divert pain and provide relaxation to children so that it can relieve tension and stress felt by children. The aim is to obtain "Implementation of Lego Play Therapy in Child Patients Undergoing Hospitalization with Anxiety Problems at GMIM Pancaran Kasih General Hospital Manado". Method used in this research is descriptive using a case study approach. The results of this research prove that Lego Play therapy can reduce anxiety levels in children undergoing hospitalization. The conclusion is that after implementing Lego play therapy, subject 1 and subject 2 experienced changes. Suggestion increase insight, knowledge, as well as broader experience in reducing the level of anxiety experienced by preschool-aged children who are hospitalized.